13.7k views
0 votes
Simplify


{x}^(5) / {y}^(2) * {x}^(3) * {y}^(5)
And animexcartoons209 please don't use PHOTOMATH...


2 Answers

5 votes

Answer:

x⁸y³

Explanation:

x⁵ ÷ y² × x³ × y⁵

It will be easier to solve this problem if you first rearrange the expression to associate like terms.

(x⁵ × x³) × (y⁵ ÷ y²)

Now, you can use the rules of exponents: When multiplying, you add exponents; when dividing, you subtract exponents.

x⁵ × x³ = x⁵⁺³ = x⁸

y⁵ ÷ y² = y⁵⁻² = y³

Thus,

(x⁵ × x³) × (y⁵ ÷ y²) = x⁸y³

User Elliott Hill
by
5.9k points
3 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] ~\dotfill\\\\ x^5/ y^2* x^3* y^5\implies \cfrac{x^5}{y^2}\cdot x^3\cdot y^5\implies x^5\cdot y^(-2)\cdot x^3\cdot y^5 \\\\\\ x^(5+3)y^(-2+5)\implies x^8y^3

User Tyler Morales
by
5.5k points